Penerapan Chatbot Auto Reply pada Telegram terhadap Pengembangan Bisnis Penjualan Sepatu Menggunakan Artificial Intelligence Markup Language - Fransisco, Fransisco; Akbar, Faris; Kurniasari, Sischa; Hibban, Muhammad Ibnu; Desyani, Teti; Nirmala, Endar (Program Studi Teknik Informatika Universitas Pamulang, 2022)
The imbalance in the number of workers and customer demand is a problem that must be faced by business actors today. With a chatbot, it can help business people handle thousands of chats from customers who want to ask about sales products. Chatbots can also save on operational costs and provide 24/7 active service. Indirectly this can provide customer connection to the store. Therefore, this study will discuss the Application of the Auto Reply Chatbot on Telegram to the Development of a Shoe Sales Business Using Artificial Intelligence Markup Language. This system involves a shoe sales information system website as a medium to provide services to customers related to sales information. And a chatbot that implements an AIML (Artificial Intelligence Markup Language) system as a virtual assistant that connects customers and information from the database. Where this chatbot will respond to conversations submitted by customers, besides that it can also retrieve data in the form of information in sales data. The system which is designed using the Javascript, PHP, Python, PDO, and MySQL programming languages as the database.System testing will show that the sales information system website is functioning properly in managing (Create, Read, Update, Delete) customer data, stock of goods, goods sold and other data, while the Chatbot test shows that the program can respond via the Telegram application, starting from messages asking for stock, item prices or requesting information from the database.